Parasitoid avoidance of intraguild predation drives enemy complementarity in a multi‐trophic ecological network - Andrew B. Hennessy; Riley M. Anderson; Nora Mitchell; Kailen A. Mooney; Michael S. Singer (Ecology, 2025)
How consumer diversity determines consumption efficiency is a central issue in ecology. In the context of predation and biological control, this relationship concerns predator diversity and predation efficiency. Reduced predation efficiency can result from different predator taxa eating each other in addition to their common prey (interference due to intraguild predation). By contrast, multiple predator taxa with overlapping but complementary feeding niches can generate increased predation efficiency on their common prey (enemy complementarity). When viewed strictly from an ecological perspective, intraguild predation and enemy complementarity are opposing forces. However, from an evolutionary ecology perspective, predators facing strong intraguild predation may evolve traits that reduce their predation risk, possibly leading to niche complementarity between enemies; thus, selection from intraguild predation may lead to enemy complementarity rather than opposing it. As specialized predators that live in or on their hosts, parasitoids are subjected to intraguild predation from generalist predators that consume the parasitoids' hosts. The degree to which parasitoid–predator interactions are ruled by interference versus enemy complementarity has been debated. Here, we address this issue with field experiments in a forest community consisting of multiple species of trees, herbivorous caterpillars, parasitoids, ants, and birds. Our experiments and analyses found no interference effects, but revealed clear evidence for complementarity between parasitoids and birds (not ants). Parasitism rates by hymenopterans and dipterans were negatively associated with bird predation risk, and the variation in the strength of this negative association suggests that this enemy complementarity was due to parasitoid avoidance of intraguild predation. We further argue that avoidance of intraguild predation by parasitoids and other arthropod predators may explain enigmatic patterns in vertebrate–arthropod–plant food webs in a variety of terrestrial ecosystems.